The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1121/1.3672697
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cochlear implants on children’s perception and production of speech prosody

Abstract: Japanese 5- to 13-yr-olds who used cochlear implants (CIs) and a comparison group of normally hearing (NH) Japanese children were tested on their perception and production of speech prosody. For the perception task, they were required to judge whether semantically neutral utterances that were normalized for amplitude were spoken in a happy, sad, or angry manner. The performance of NH children was error-free. By contrast, child CI users performed well below ceiling but above chance levels on happy- and sad-soun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
83
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(102 citation statements)
references
References 30 publications
10
83
1
Order By: Relevance
“…This finding both supports and extends upon previous literature that has shown that imitation is problematic for children with hearing loss (Chin et al, 2012;Cleary et al, 2002;Dillon et al, 2004;Ertmer & Goffman, 2011;Ertmer et al, 1997;Nakata et al, 2012;Peng et al, 2008;Sehgal et al, 1998). For example, children with hearing loss have been shown to have difficulty producing exact imitations of non-words, and their attempted repetitions tended to have fewer syllables as compared to the target (Cleary et al, 2002;Dillon et al, 2004).…”
Section: Infant and Mother Vocalizationssupporting
confidence: 79%
See 3 more Smart Citations
“…This finding both supports and extends upon previous literature that has shown that imitation is problematic for children with hearing loss (Chin et al, 2012;Cleary et al, 2002;Dillon et al, 2004;Ertmer & Goffman, 2011;Ertmer et al, 1997;Nakata et al, 2012;Peng et al, 2008;Sehgal et al, 1998). For example, children with hearing loss have been shown to have difficulty producing exact imitations of non-words, and their attempted repetitions tended to have fewer syllables as compared to the target (Cleary et al, 2002;Dillon et al, 2004).…”
Section: Infant and Mother Vocalizationssupporting
confidence: 79%
“…Although this study did not examine what vowels and consonants NH and HI groups imitated, the findings of this study add to the previous studies (Chin et al, 2012;Cleary et al, 2002;Dillon et al, 2004;Ertmer & Goffman, 2011;Ertmer et al, 1997;Nakata et al, 2012;Peng et al, 2008;Sehgal et al, 1998) by showing that the quantity of utterances with matched sounds is affected by infant hearing status.…”
Section: Infant and Mother Vocalizationsmentioning
confidence: 45%
See 2 more Smart Citations
“…Much of the recent research on music with hearing loss has focused on the emerging technologies related to cochlear implants, while some studies look particularly at hearing loss with just hearing aids, such as in the description of how people with hearing aids listen to music from an audiological perspective [34,35]. Music perception by cochlear implant users has been observed both by otolaryngology laboratories [36][37][38] and by psychologists' groups [39,40].…”
Section: Hearing Loss Music Listening and Music Trainingmentioning
confidence: 99%